The effects of baicalein extracted from oroxylum indicum leaves on neural stem cell gene expression - Sivalingam, Theanpriah (2023)
Ischemic stroke is a cerebral dysfunction caused by the blockage of an artery in the brain. The pathophysiological events after ischemic stroke result in cell death, neurological deficits, and brain injury. Although several ischemic stroke treatments are currently available, they are limited by the ability to regenerate the damaged or dysfunctional brain tissue in the ischemic brain. Hence, regenerative therapy using neural stem cells (NSCs) can be applied to ischemic stroke treatment as it has the ability to repair, replace and regenerate the affected region in the brain. However, regenerative treatment using NSCs has a low cell survival rate after being transplanted into the ischemic brain due to oxidative stress and inflammatory response. Therefore, the present study utilized a preconditioning strategy using baicalein, a flavonoid to investigate whether it can enhance the therapeutic properties of NSCs. This study aimed to determine the effects of baicalein extracted from Oroxylum indicum on the therapeutic potential of NSCs for ischemic stroke by elucidating the gene expression. The findings showed that Angiopoietin 1 (ANGPT1) (p = 0.00001) was significantly upregulated with the highest fold change which is 5.9 followed by Superoxide dismutase 2 (SOD2) (p = 0.000003) with fold change 3.4 indicating that fractionated baicalein can promote angiogenesis and antioxidant properties in NSCs for ischemic stroke. Besides, Neuroepithelial stem cell protein (NESTIN) (p = 0.039) and SRY-box transcription factor 2 (SOX2) (p = 0.023) were significantly upregulated with fold change 1.61 and 1.25 respectively, indicating that fractionated baicalein extract could improve the stemness property of NSCs. Gamma-aminobutyric acid type A receptor subunit alpha 6 (GABRA6) (p=0.045) also showed significant upregulation suggesting that baicalein can potentially reduce excitotoxicity in NSCs caused by ischemic stroke. However, unexpected result was obtained in the expression of Interleukin 1 receptor antagonist (IL-1RN). This gene did not show any significant effect in the treated samples which demonstrates that IL-1RN might not contribute in reducing inflammation in NSCs. In conclusion, this study presented that baicalein active compound could enhance revascularization, antioxidant properties, self-renewal, and reduce excitotoxicity in NSCs.